Countering terrorism or criminalizing curiosity? the troubled history of UK responses to right-wing and other extremism - Zedner, L (SAGE Publications, 2021)
The growth of right-wing extremism, especially where it segues into hate crime and terrorism, poses new challenges for governments, not least because its perpetrators are typically lone actors, often radicalized online. The United Kingdom has struggled to define, tackle or legitimate against extremism, though it already has an extensive array of terrorism-related offences that target expression, encouragement, publication and possession of terrorist material. In 2019, the United Kingdom went further to make viewing terrorist-related material online on a single occasion a crime carrying a 15-year maximum sentence. This article considers whether UK responses to extremism, particularly those that target non-violent extremism, are necessary, proportionate, effective and compliant with fundamental rights. It explores whether criminalizing the curiosity of those who explore radical political ideas constitutes legitimate criminalization or overextends state power and risks chilling effects on freedom of speech, association, academic freedom, journalistic enquiry and informed public debate—all of which are the lifeblood of a liberal democracy.